Primary caregivers’ perceptions of the effect of COVID-19 on the mental well-being of learners at a secondary school in Soweto - Maseko, Nokuthula (University of the Witwatersrand, Johannesburg, 2024)
During the COVID-19 pandemic in March 2020 lockdown restrictions were introduced in South Africa and around world. This led to school closures as well. During this period learners around the world experienced mental-health challenges due to the restrictions on gatherings, school attendance as well as social distancing. Some of the mental-health challenges that affected the learners include depression, anxiety, sleeping disorders as well as weight gain. This study explored the perceptions of the primary caregivers of secondary school learners in Soweto on the mental well-being of learners during the COVID-19 lockdown. The study was conducted using an ecological theoretical framework which looked at the relationship of the learner in relation to different systems that they interact with. The researcher used a qualitative research approach and a phenomenographic research design. Purposive sampling was utilised to select the sample of 8 primary caregivers of grade 11 learners at a Secondary School in Soweto. Semi-structured interviews were the method of data collection and a semi-structured interview schedule was used as the research instrument. Data collected was coded, themed, and analysed using reflective thematic analysis. The results from this study showed how COVID-19 had a negative effect on the academic performance of learners. The learners still could not achieve pre-COVID-19 results even after efforts were made for after-school programs and catch-up sessions. The learners' attitudes towards the virus included fear of death or losing loved ones due to COVID-19 as well as confusion and fear of contracting the virus. The learners shared that coughing, sneezing, or the mere sight of a tissue triggers them to date as they associate such symptoms with COVID-19. The learners in this study experienced psycho-social effects such as anxiety and stress as well as physical challenges such as weight gain, migraines, sleeping challenges as well as communication issues with the family members. Social media and technology acted as a buffer for learners as it offered them information, knowledge as well as social connections with teachers, peers, friends, and extended family members. The importance of working in a multi-disciplinary team to support and foster resiliency for the learners is highlighted. The learners in Soweto had their own experiences, but they were similar to those from around the world and therefore one can conclude that pandemic experiences were generic to some extent.
A research report Submitted in fulfillment of the requirements for a Master of Arts in Social Work , In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Primary caregivers; COVID-19; Learners; Mental-wellbeing; Secondary School; SDG-3: Good health and well-being